A Review of Carbon Dynamics and Sequestration in Wetlands - Adhikari, Shalu; Bajracharaya, Roshan M; Sitaula, Bishal K (Journal of Wetlands Ecology, 2009)
Wetlands are among the most important natural resources on earth. They provide a potential sink for atmospheric carbon but if not managed properly, they become a source of green house gases. However, only limited studies have been conducted to assess the roles and potentials of wetlands in carbon sequestration. Wetlands occupy approximately 5% of the total land area in Nepal, some of these being of international importance. However, there are major knowledge gaps in accurately quantifying carbon stored in them, as well as their carbon sequestration potential. Therefore, further research is needed to better understand the processes of carbon sequestration in wetland vegetation and soils. Key words: wetland, sink, carbon sequestration DOI: 10.3126/jowe.v2i1.1855 Journal of Wetlands Ecology, (2009) vol. 2, pp 41-45